(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The School Management System - BCPMAS (Academic Management System) Project proposed to make the work of School Academic Management more efficient in Scheduling and Grade managing the student records of a school in Bestlink College of the Philippines (BCP). The Academic Management system’s goal is to make the transactions easier for users like Admin, Program heads, Strand Heads, and Dean. This system will help them manage every transaction in the specific management more efficiently. Throughout the development process, the team saw several opportunities to create a better and more unique system for department heads and users. Academic Management System is a Web-based system that can manage School Management, Faculty List Reports, Grade management, and Report Monitoring. The students, teachers, and supporting learning activities and modalities are the primary focus of the BCPAMS Project.